Sustainable ocean governance : a geographical perspective - Vallega, Adalberto (Ocean management and policy series., 2002)
This topical book examines ocean governance and calls for close co-operation between science and policy. Adalberto Vallega uniquely considers the ocean as a spatial complex system which must be represented as a whole and argues that scientific approaches must change to achieve progress and co-operation between science and policy.